PREVALENSI STRONGYLOSIS PADA PEDET DI KABUPATEN KLATEN, JAWA TENGAH - , VEGA SALSABELLA RAHAJENG ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Strongylosis in calves measure a great lost for farmers. The objectives of this study were measure the prevalence of the strongylosis and indentify risk factors associated with strongylosis in Klaten. A total of 214 fecal samples were selected by multistage random sampling, random sampling, cluster from six subdistricts from Klaten regency. Risk factors collected using questioner list. Laboratory diagnose based on floatation method at Balai Besar Veteriner Laboratory Wates. Data were analyzed by statistic descriptive and the association between risk factors and strongylosis was done by chi-square and the strenght of association measured by odds ratio. The results reveal a strongylosis prevalence of 10,3% among calves in Klaten. Based on bivariate analysis, risk factors associated with strongylosis were forage from outside the village, fecal collection, and fecal processing.